Influência do tratamento de superfície e do tipo de cimento na retenção de coroas YTZP - Rippe, Marília Pivetta [UNESP] (2013)
To compare the retention of YTZP zirconia crowns cemented to different cementation protocols. 108 extracted molars were prepared for full crown (n = 12); and the core was reconstructed with glass fiber post and composite resin core. YTZP zirconia copings were milled and 72 specimens were divided into 6 groups according to the factors: cements- Multilink (Mult) and Relyx ARC (Rel); and zirconia surface treatments- alcohol (control) (C), silica coating (S) and vitrification (V). The remaining 36 specimens were divided into 3 groups cemented with Relyx Luting (Ion), Relyx U100 (Self) and Zinc phosphate (Zinc) on untreated zirconia. The specimens were thermally cycled (5 - 55 °C, 6000 cycles) and data from the tensile test were analyzed by Kruskal Wallis and Dunn test. The median and interquartil range were: MultC: 20.0 (± 5.5); MultS: 28.5 (± 22.0); MultV: 32.5 (± 28.5); RelC: 21.5 (± 8.5); RelS: 22.0 (± 10.0); RelV: 24.0 (± 7.3); Ion: 5.1 (± 6.4); Self: 3.5 (± 5.2); Zinc: 7.7 (± 14.2). The type of resin cement (BIS-GMA- or HEMA- based) did not affect the crown retention values. The treatment involving vitrification of the cementation surface was only capable to improve the retention force for the HEMA based-cement. For untreated intaglio surfaces of YTZP crowns, resin cements showed significantly higher retention than those obtained for self-adhesive, glass ionomer and zinc phosphate cements